Educating for critical thinking in university: The criticality of critical thinking in education and everyday life - Franco, Amanda (2018)
Nowadays, both on-line and "off-line" lives seem to be bound to the terms of democratization of information. While this brings clear advantages, does free and fast access to plenty of information entail that individuals are better informed and well-equipped to think reasonably, make decisions, and solve problems? In a time apparently governed by fraudulent decision-makers, floppy media, fake news, and frantic information, it is essential to know how to think critically. Critical thinking is crucial along schooling, in the world of work, in personal everyday life, and in life as members of a society. Nonetheless, critical thinking is not innate and effortless; it must be developed and mobilized with deliberation in a systematic way. Researchers and international agencies agree that it is critical to have critical thinking to face present-futurist challenges such as the United Nation's 17 Sustainable Development Goals. But before individuals learn to become critical thinkers, teachers themselves need teacher education opportunities to learn how to use their critical thinking abilities, and how to spark students' critical thinking potential and promote it. Here, the role played by education in developing critical thinking is stressed, and specific teaching-learning strategies that have shown to be effective are identified.